The Influence of Work Environment and Workload on Employee Performance with Work Motivation as an Intervening Variable at the Department of Population and Civil Registration of Pematangsiantar City - Arjunansi Samosir; Sarida Sirait; Hengki Mangiring Parulian Simarmata (Journal of Management and Business Analytics, 2026)
The purpose of this study is to find out the influence of work environment and workload on employee performance with work motivation as an intervening variable at the Population and Civil Registration Office of Pematangsiantar City. This study uses quantitative descriptive. The population used in this study is all employees of the Population and Civil Registration Office of Pematangsiantar City which is 46 people who work in all divisions. The data collection technique uses questionnaires. The results of this study show that the work environment has a positive but insignificant effect on employee performance, the work environment has a positive and significant effect on work motivation, workload has a positive but insignificant effect on employee performance, workload has a positive and significant effect on work motivation, work motivation has a positive and significant effect on employee performance, work environment has a positive and significant effect on performance Employees through work motivation, workload has a positive but not significant effect on employee performance through motivation.